The interaction between Sertoli cells and luekemia inhibitory factor on the propagation and differentiation of spermatogonial stem cells in vitro - Tayebeh Rastegar; Mehryar Habibi Roudkenar; Soraya Parvari; Maryam Baazm (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Sertoli cells play a pivotal role in creating microenvironments essential for spermatogonial stem cells (SSCs) self-renewal and commitment to differentiation. Maintenance of SSCs and or induction of in vitro spermiogenesis may provide a therapeutic strategy to treat male infertility. Objective: This study investigated the role of luekemia inhibitory factor (LIF) on the propagation of SSCs and both functions of Sertoli cells on the proliferation and differentiation of these cells. Materials and Methods: SSCs were sorted from the testes of adult male mice by magnetic activated cell sorting and thymus cell antigen 1 antibody. On the other hand, isolated Sertoli cells were enriched using lectin coated plates. SSCs were cultured on Sertoli cells for 7 days in the absence or presence of LIF. The effects of these conditions were evaluated by microscopy and expression of meiotic and post meiotic transcripts by reverse transcriptase polymerase chain reaction. Results: Our data showed that SSCs co-cultured with Sertoli cells in the presence of LIF formed colonies on top of the Sertoli cells. These colonies had alkaline phosphatesase activity and expressed SSCs specific genes. SSCs were enjoyed limited development after the mere removal of LIF, and exhibiting expression of meiotic and postmeiotic transcript and loss of SSCs specific gene expression (p< 0.05). Conclusion: Our findings represent co-culture of SSCs with Sertoli cells provides conditions that may allow efficient proliferation and differentiation of SSCs for male infertility treatment.